Dysregulated naive B cells and de novo autoreactivity in severe COVID-19 - Woodruff, Matthew C.; Ramonell, Richard P.; Haddad, Natalie S.; Anam, Fabliha A.; Rudolph, Mark E.; Walker, Tiffany A.; Truong, Alexander D.; Dixit, Adviteeya N.; Han, Jenny E.; Cabrera-Mora, Monica; Runnstrom, Martin C.; Bugrovsky, Regina; et al. (Nature (London), 2022)
Severe SARS-CoV-2 infection 1 has been associated with highly inflammatory immune activation since the earliest days of the COVID-19 pandemic 2 – 5 . More recently, these responses have been associated with the emergence of self-reactive antibodies with pathologic potential 6 – 10 , although their origins and resolution have remained unclear 11 . Previously, we and others have identified extrafollicular B cell activation, a pathway associated with the formation of new autoreactive antibodies in chronic autoimmunity 12 , 13 , as a dominant feature of severe and critical COVID-19 (refs. 14 – 18 ). Here, using single-cell B cell repertoire analysis of patients with mild and severe disease, we identify the expansion of a naive-derived, low-mutation IgG1 population of antibody-secreting cells (ASCs) reflecting features of low selective pressure. These features correlate with progressive, broad, clinically relevant autoreactivity, particularly directed against nuclear antigens and carbamylated proteins, emerging 10–15 days after the onset of symptoms. Detailed analysis of the low-selection compartment shows a high frequency of clonotypes specific for both SARS-CoV-2 and autoantigens, including pathogenic autoantibodies against the glomerular basement membrane. We further identify the contraction of this pathway on recovery, re-establishment of tolerance standards and concomitant loss of acute-derived ASCs irrespective of antigen specificity. However, serological autoreactivity persists in a subset of patients with postacute sequelae, raising important questions as to the contribution of emerging autoreactivity to continuing symptomology on recovery. In summary, this study demonstrates the origins, breadth and resolution of autoreactivity in severe COVID-19, with implications for early intervention and the treatment of patients with post-COVID sequelae. Single-cell B cell repertoire analysis identifies the expansion of a naive-derived population of antibody-secreting cells contributing to de novo autoreactivity in patients with severe COVID-19 and those with post-COVID symptoms.